Dapagliflozin in Patients with Chronic Kidney Disease - Heerspink, Hiddo J.L; Stefánsson, Bergur V; Correa-Rotter, Ricardo; Chertow, Glenn M; Greene, Tom; Hou, Fan-Fan; Mann, Johannes F.E; McMurray, John J.V; Lindberg, Magnus; Rossing, Peter; Sjöström, C. David; Toto, Roberto D; et al. (The New England journal of medicine, 2020)
In this trial, patients with CKD (with or without type 2 diabetes) were randomly assigned to receive dapagliflozin or placebo. The primary composite outcome — a sustained decline in the estimated GFR of at least 50%, end-stage kidney disease, or death from renal or cardiovascular causes — was less frequent with dapagliflozin.